2015
DOI: 10.1088/0004-6256/149/2/46
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Epoch Multi-Frequency Vlbi Study of the Parsec-Scale Jet in the Blazar 3c 66a

Abstract: We present the observational results of the γ-ray blazar, 3C 66A, at 2. 3, 8.4, and 22 GHz at 4 epochs during 2004-05 with the VLBA. The resulting images show an overall core-jet structure extending roughly to the south with two intermediate breaks occurring in the region near the core. By model-fitting to the visibility data, the northmost component, which is also the brightest, is identified as the core according to its relatively flat spectrum and its compactness. As combined with some previous results t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…They are in good agreement with previous results from the same data sets (Cai et al 2007;Zhao et al 2014). The final solutions for the amplitude and phase obtained by self-calibration of 3C 66A for a time interval of 0.1 min were applied to the 3C 66B data to calibrate the results for short period variations due to atmospheric effects.…”
Section: Observations and Data Reductionsupporting
confidence: 83%
See 1 more Smart Citation
“…They are in good agreement with previous results from the same data sets (Cai et al 2007;Zhao et al 2014). The final solutions for the amplitude and phase obtained by self-calibration of 3C 66A for a time interval of 0.1 min were applied to the 3C 66B data to calibrate the results for short period variations due to atmospheric effects.…”
Section: Observations and Data Reductionsupporting
confidence: 83%
“…In this paper, we focus on the improvement in the image quality, and we will present the astrometric results in a separate paper. The 22 GHz observations consisted of nodding-mode observations of 3C 66A and 3C 66B with a switching cycle of 30 s. 3C 66A is a very bright quasar exhibiting a compact core and one-sided southward jet (Taylor et al 1996;Jorstad et al 2001;Cai et al 2007;Zhao et al 2014). Since this source is very close in the sky to 3C 66B (∼ 0.1 degree, it is a very good source for phase and amplitude calibration of 3C 66B.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Furthermore, there might be contributions from the reference source in the measurements because it is variable. Especially, follow-up studies have found apparent inward motions of the innermost components in the jet of 3C 66A which supports the later argument (See Figure 3 in [4]).…”
Section: Introductionsupporting
confidence: 76%
“…Together, both these effects might be responsible for the subdued INOV of BAL_blazar candidates, as found here. In this context, it would be particularly useful to carry out multi-epoch VLBI imaging of BAL_blazar candidates, in search of evidence for systematically lower jet speeds and also for measuring the brightness temperatures and flux variability of their VLBI cores, towards obtaining the much needed estimates of the jets' Doppler factors (e.g., Zhao et al 2015). Equally, it would be desirable to employ larger telescopes to extend the INOV search to larger (likely, fainter) samples of BAL_blazar candidates, for a more robust characterization of their INOV.…”
Section: Discussionmentioning
confidence: 99%